Proteomic Insights of Cowpea Response to Combined Biotic and Abiotic Stresses - Daiane Gonzaga Ribeiro; Ana Carolina Mendes Bezerra; Ivonaldo Reis Santos; Priscila Grynberg; Wagner Fontes; Mariana de Souza Castro; Marcelo Valle de Sousa; Maria Eugênia Lisei-de-Sá; Maria Fatima Grossi-de-Sá; Octávio Luiz Franco; Angela Mehta (Plants, 2023)
The co-occurrence of biotic and abiotic stresses in agricultural areas severely affects crop performance and productivity. Drought is one of the most adverse environmental stresses, and its association with root-knot nematodes further limits the development of several economically important crops, such as cowpea. Plant responses to combined stresses are complex and require novel adaptive mechanisms through the induction of specific biotic and abiotic signaling pathways. Therefore, the present work aimed to identify proteins involved in the resistance of cowpea to nematode and drought stresses individually and combined. We used the genotype CE 31, which is resistant to the root-knot nematode Meloidogyne spp. And tolerant to drought. Three biological replicates of roots and shoots were submitted to protein extraction, and the peptides were evaluated by LC-MS/MS. Shotgun proteomics revealed 2345 proteins, of which 1040 were differentially abundant. Proteins involved in essential biological processes, such as transcriptional regulation, cell signaling, oxidative processes, and photosynthesis, were identified. However, the main defense strategies in cowpea against cross-stress are focused on the regulation of hormonal signaling, the intense production of pathogenesis-related proteins, and the downregulation of photosynthetic activity. These are key processes that can culminate in the adaptation of cowpea challenged by multiple stresses. Furthermore, the candidate proteins identified in this study will strongly contribute to cowpea genetic improvement programs.